Dora Enterprise "Dorayaki" / Stefanie Lynn Dangatil... [et al.] - Dangatil, Stefanie Lynn; Vitalis, Sharly; Johnny, Vevian Sherley; Stephen, Noritah Cin (2010)
The name of Dorayaki cake is familiar to us. This is because these pancakes are often consumed by Nobita, a cartoon character in Doreamon hit. Dorayaki is very popular in Japan. Even now, its popularity has spread to countries in other Asian. Dorayaki is belong to the category of the traditional Japanese cake (Wagashi) that looks a bit chubby round, consisting of two pieces glued cake with red bean paste. In addition there are variations in original taste of Dorayaki such as Dorayaki red beans and Dorayaki chocolate. We have determined to produce Dorayaki with variety of taste as our product. We choose this product so that we can commercialize it throughout Sabah. Malaysia and even overseas. Dorayaki is a type of Japanese confection which consists of two small pancakes like patties made from castella wrapped around a filling of sweet red bean paste. Incidentally, Castella is a popular Japanese sponge cake made of sugar, flour, eggs, and starch syrup, very common at festivals and as a street food. It originally only had one layer, and the current shape was invented in 1914 by Ueno Usagiya. In Japanese, dora means "gong", and because of the similarity of the shapes, this is probably the origin of the name of the sweet. Legend has it that the first Dorayaki were made when a samurai named Benkei forgot his gong (dora) upon leaving a farmer's home where he was hiding and the farmer subsequently used the gong to fry the pancakes, thus the name Dorayaki. Even though there are already existed Dorayaki in this business field, but we try to overcome the weaknesses of them by introducing different types of filling of Dorayaki which we use fruits jam, chocolate, cheese, green tea cream and so on. Through our business plan, also from our commitment, cooperation and proper management we hope to operate our business smoothly and be a successful manufacturing entity.